Five fall into adventure - Blyton, Enid. (b, 2004)
George and Timmy the dog have disappeared - and somebody has broken into Kirrin Cottage! The Famous Five are sure there's a connection - but how can they solve the mystery when there are only three of them?
Keywords: Famous Five (Fictitious characters) -- Juvenile fiction; Kidnapping -- Fiction; Vacations -- Fiction